3.6 and 4.5 Micron Phase Curves and Evidence for Non-Equilibrium Chemistry in the Atmosphere of Extrasolar Planet HD 189733b - Knutson, H; Lewis, N; Fortney, J; Burrows, A; Showman, A; Cowan, N; Agol, E; Aigrain, S; Charbonneau, D; Deming, D; Desert, J; Henry, G; et al. (Institute of Physics Publishing, 2012)
We present new, full-orbit observations of the infrared phase variations of the canonical hot Jupiter HD 189733b obtained in the 3.6 and 4.5 micron bands using the Spitzer Space Telescope. When combined with previous phase curve observations at 8.0 and 24 micron, these data allow us to characterize the exoplanet's emission spectrum as a function of planetary longitude. We utilize improved methods for removing the effects of intrapixel sensitivity variations and accounting for the presence of time-correlated noise in our data. We measure a phase curve amplitude of 0.1242% +/- 0.0061% in the 3.6 micron band and 0.0982% +/- 0.0089% in the 4.5 micron band. We find that the times of minimum and maximum flux occur several hours earlier than predicted for an atmosphere in radiative equilibrium, consistent with the eastward advection of gas by an equatorial super-rotating jet. The locations of the flux minima in our new data differ from our previous observations at 8 micron, and we present new evidence indicating that the flux minimum observed in the 8 micron is likely caused by an over-shooting effect in the 8 micron array. We obtain improved estimates for HD 189733b's dayside planet-star flux ratio of 0.1466% +/- 0.0040% at 3.6 micron and 0.1787% +/- 0.0038% at 4.5 micron; these are the most accurate secondary eclipse depths obtained to date for an extrasolar planet. We compare our new dayside and nightside spectra for HD 189733b to the predictions of models from Burrows et al. (2008) and Showman et al. (2009). We find that HD 189733b's 4.5 micron nightside flux is 3.3 sigma smaller than predicted by the Showman et al. models, which assume that the chemistry is in local thermal equilibrium. We conclude that this discrepancy is best-explained by vertical mixing, which should lead to an excess of CO and correspondingly enhanced 4.5 micron absorption in this region. [abridged]